Investigation of High School Students' Orientation to Leisure Sportive Activities and Leisure Involvement Levels - Kilicarslan, Ferhat; Durhan, Tebessüm Ayyildiz; Kurtipek, Serkan (PT. Riset Press International, 2025)
The purpose of this study is to examine the orientation toward sports activities, leisure involvement, and participation levels in sports activities during leisure time among high school students who participate in outdoor sports activities. In this context, a total of 228 high school students, 127 female and 101 male, participated in the study. Data for the study were collected through face-to-face interviews using questionnaires. Since the collected data were found to be within the parameters of normal distribution, parametric tests were applied. According to the findings, high school students were found to have high levels of orientation toward sports activities and free time. In addition, it was determined that students' gender, perceived income levels, daily free time duration, and the type of activity most preferred during free time significantly differentiated their orientation toward sports activities and levels of interest in free time. Furthermore, leisure involvement levels account for 39% of the variance in participation levels in sports activities. Based on these results, it can be said that high school students can socialize and develop their knowledge by participating in sports activities during their free time. In this regard, it is recommended that organizations be established to help high school students use their time after school more productively and in a way that is filled with sports activities.